Agronomic and environmental aspects of organo-mineral fertilizers produced with a by-product of the intermediate process of tanning - Lima, Francielle Roberta Dias de; Silva, Aline Oliveira; Amorim, Helen Carla Santana; Figueredo, Eduardo Sobrinho Santos; Carneiro, Rafael Marta Carbone; Jara, Madeliny Saracho; Carneiro, Marco Aurélio Carbone; Guilherme, Luiz Roberto Guimarães (Frontiers in Agronomy, 2023)
The by-product of the intermediate process of tanning (BPIPT) can be used in the manufacturing of environmentally-friendly organo-mineral fertilizers (OMF). However, the presence of potentially toxic elements (e.g., chromium, Cr), can hinder the use of BPIPT in agriculture. This study aimed: i) to evaluate soil chemical and biological properties following the application of fertilizers produced with a BPIPT, in contrast to other OMF produced with traditional organic matrices; and ii) to assess the impacts of such products on wheat growth and nutrition. Samples (0-0.2 m) of two Oxisols [Red-Yellow Latosol (LVAd) and Red Latosol (LVd)] were used in this study, consisting of two experiments (with five treatments and five replicates) using different OMF, in a sequence: 1) incubation of fertilizers in soil samples for 30 days, and 2) wheat cultivation (30 days) after the fertilizer incubation. The treatments consisted of an arrangement of mineral fertilizers based on nitrogen, phosphorus, and potassium (NPK fertilizers), associated with OMF based on BPIPT (OM-IPT and OM-IPT+S) or commercial manure (OM-CM and OM-CM+S), with or without sulfur (S), and a control treatment. Elemental availability in soils and microbial attributes were determined after the incubation of the OMF in the soils. After wheat cultivation, plant biomass, nutritional composition, β-glucosidase activity, and fluorescein diacetate hydrolysis (FDA) were measured. The application of BPIPT-derived OMF in the present study increased available Cr fraction contents in both soils. However, OM-IPT it caused low soil acidification, enhanced wheat growth and nutrition, and stimulated microbial activity in soils (FDA and β-glucosidase), thus evidencing the agronomic and environmental benefits of this OMF and their potential to contribute to a cleaner, more sustainable agriculture.